Peran welas diri terhadap pengungkapan kesulitan pada individu dewasa awal dari keluarga yang bercerai - Nathalie, Giftania Grace; Dicky Sugianto (Konsorsium Psikologi Ilmiah Nusantara, 2024)
Emerging adults who experienced parental divorce may face interpersonal difficulties, which can manifest as reduced distress disclosure. This study examines the role of self-compassion in distress disclosure among emerging adults with a history of parental divorce. A simple linear regression analysis was conducted on data collected from a survey of 128 young adults who had experienced parental divorce prior to the age of 16. Results indicate that, at an overall level, self-compassion did not significantly predict distress disclosure among emerging adults who experienced parental divorce. However, additional analysis suggests that the overidentification component of self-compassion correlated positively with distress disclosure. The duration of parental divorce (the time that had passed since the divorce) was positively correlated with overall self-compassion and the mindfulness component of self compassion, while correlating negatively with the self-judgment component of self-compassion. Cultural differences may explain these findings, where individuals in individualistic cultures tends to disclose difficulties to others, while those in collectivits cultures may supress such experiences.